Mnożenie jednomianów przez sumy algebraiczne.

Wykonaj działania

a) 6(x - 4) - 2 =
b) 2(x + 1) - 3(x - 1) =
c) -3(y -2) + 4(y +2) =
d) 5(x - y -1) - 4(x + 2) =
e) 2(3a + b) - 2(a -b) =
f) jedna druga(4x - 4) - 2x =
g) x(x - 1) - 3(x do potegi drugiej - x)
h) 5a(a - 3) - 3a(a - 5) =

2

Odpowiedzi

2010-01-18T22:02:29+01:00
A) 6x - 24 - 2 = 6x - 26
b) 2x + 2 -3x + 3 = -x +5
c)-3y + 5 +4y + 8 = y + 13
d) 5x - 5y - 5 - 4x - 8 = x - 5y - 13
e) 6a + 2b - 2a + 2b = 4a + 4b
f) 2x - 2 - 2x = -2
g) x - x - 3xkwadrat + 3x = x
h) 5akwadrat - 15a - 3akwadrat + 15 = -13a + 15
5 4 5
Najlepsza Odpowiedź!
2010-01-18T22:10:22+01:00
A) 6(x - 4) - 2 = 6x-24-2= 6x-26=2(3x-13)
b) 2(x + 1) - 3(x - 1) = 2x+2-3x+3=-x+5
c) -3(y -2) + 4(y +2) = -3y+6+4y+8=y+14
d) 5(x - y -1) - 4(x + 2) = 5x-5y-5-4x-8=x-5y-13
e) 2(3a + b) - 2(a -b) = 6a+2b-2a+2b=4a+4b=4(a+b)
f) jedna druga(4x - 4) - 2x = 2x-2-2x=-2
g) x(x - 1) - 3(x do potegi drugiej - x) = x^2-x-3x^2+3x=-2x^2+2x=-2x(x-1)
h) 5a(a - 3) - 3a(a - 5) =5a^2-15a-3a^2+15a=2a^2
2 3 2